2011
DOI: 10.1007/s12046-011-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influential parameters of machining of AISI 304 stainless steel

Abstract: Austenitic stainless steels are hard materials to machine, due to their high strength, high ductility and low thermal conductivity. The last characteristic results in heat concentration at the tool cutting edge. This paper aims to optimize turning parameters of AISI 304 stainless steel. Turning tests have been performed in three different feed rates (0.2, 0.3, 0.4 mm/rev) at the cutting speeds of 100, 125, 150, 175 and 200 m/min with and without cutting fluid. A design of experiments (DOE) and an analysis of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…Further, AlCrN/TiAlN coated cutting tools gave lower cutting forces due to the lower friction coefficient of the coating. Mahdavinejad and Saeedy (2011) tried to investigate the influence of cutting conditions on machining of austenitic stainless steel with cutting fluid and in dry conditions. Authors have noted that cutting speed is the main parameter which affect flank wear and as cutting speed increases to 175 m/min, the flank wear decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Further, AlCrN/TiAlN coated cutting tools gave lower cutting forces due to the lower friction coefficient of the coating. Mahdavinejad and Saeedy (2011) tried to investigate the influence of cutting conditions on machining of austenitic stainless steel with cutting fluid and in dry conditions. Authors have noted that cutting speed is the main parameter which affect flank wear and as cutting speed increases to 175 m/min, the flank wear decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [8] was used simulation annealing algorithm to optimize the parameters of support vector machine. Mahdavinejad et al [9] optimized tuning parameters of AISI 304 stainless steel using Design of Experiment and also conducted an ANOVA test to determine the effect of each parameter on surface roughness and tool wear. Results showed that cutting speed has main influence on the flank wear and feed rate on surface roughness.…”
Section: Relational Analysismentioning
confidence: 99%
“…304 stainless steel is mainly used for Heat Exchangers, bushings, springs, bearings, gears, and shafts. Despite the increased usage of 304 stainless steel, they have relatively poor machinability characteristics compared to other metals, because of their poor thermal conductivity [4].…”
Section: Introductionmentioning
confidence: 99%